2006
DOI: 10.1073/pnas.0605421103
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic amplification of a rice transposable element during recent domestication

Abstract: Despite the prevalence of transposable elements in the genomes of higher eukaryotes, what is virtually unknown is how they amplify to very high copy numbers without killing their host. Here, we report the discovery of rice strains where a miniature invertedrepeat transposable element (mPing) has amplified from Ϸ50 to Ϸ1,000 copies in four rice strains. We characterized 280 of the insertions and found that 70% were within 5 kb of coding regions but that insertions into exons and introns were significantly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
245
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(261 citation statements)
references
References 30 publications
14
245
2
Order By: Relevance
“…Second, previous studies have demonstrated convincingly that there is selection against TEs. For example, a recent study of rice TEs found that insertions into gene regions are lost rapidly because of strong selection against the interruption of gene function (55). These highly deleterious events are not expected to rise to appreciable population frequencies and are thus unlikely to have been included in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies have demonstrated convincingly that there is selection against TEs. For example, a recent study of rice TEs found that insertions into gene regions are lost rapidly because of strong selection against the interruption of gene function (55). These highly deleterious events are not expected to rise to appreciable population frequencies and are thus unlikely to have been included in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…S3). It has been shown that the genomes of domesticated species can be expanded by dramatic amplification of TEs (39). Furthermore, retrotransposon insertions have been reported to collapse or silence genes, as exemplified by phenotypic changes in tomato fruit shape (40).…”
Section: Discussionmentioning
confidence: 99%
“…Three RT-enriched genes did show significant differences in numbers of gene copies, suggesting gene amplification following speciation. Naito et al (2006) reported dramatic amplification of a rice-transposable element designed as mPing during domestication, suggesting that the rapid increase represents a potentially valuable source of population diversity. Although the nature of the three genes that are rapidly evolving in copy number is not yet clear, ongoing analysis of the 289 family members of RT/RMI19 in the recently completed genome sequence of S. bicolor might provide clues to shed further light on genome evolution following speciation.…”
Section: Discussionmentioning
confidence: 99%